Efficacy and safety of midazolam versus dexmedetomidine in mechanically ventilated intensive care unit patients: a systematic review and meta-analysis - Peng, Wei; Lin, Yuan-Yuan; Lin, An-Ni; Zheng, Yong-Jia; Cai, Xu-Liang; Li, Yue-Fei; Tang, Qian-Yi; He, Huan (Frontiers in Pharmacology, 2026)
BackgroundMidazolam and dexmedetomidine are widely used sedatives for mechanically ventilated patients in the intensive care unit (ICU). However, their comparative effectiveness and safety remain debated. This systematic review and meta-analysis aimed to evaluate randomized controlled trials (RCTs) directly comparing these agents.MethodsThe review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. PubMed, The Cochrane Library, Web of Science, and Embase were searched through August 2025. Eligible studies were RCTs comparing midazolam with dexmedetomidine in adult ICU patients requiring invasive mechanical ventilation. Outcomes included mechanical ventilation duration, ICU length of stay, delirium, hemodynamic adverse events, and mortality. Pooled estimates were calculated using fixed- or random-effects models, with subgroup and sensitivity analyses performed to assess robustness.ResultsFifteen RCTs with diverse international populations were included. Dexmedetomidine significantly reduced mechanical ventilation duration (WMD = −0.96 days, 95% CI: −1.56 to −0.36) and lowered delirium risk (RR = 0.59, 95% CI: 0.52–0.68). It was, however, associated with a higher incidence of bradycardia (RR = 2.05, 95% CI: 1.61–2.62). No significant differences were observed in ICU length of stay (WMD = −0.89 days, 95% CI: −2.41 to 0.62) or all-cause mortality (RR = 0.96, 95% CI: 0.79–1.18). Sensitivity analyses confirmed the stability of pooled results. Subgroup analyses suggested stronger benefits of dexmedetomidine in Asian studies and in smaller trials, while the protective effect against delirium was more pronounced in older patient cohorts.ConclusionDexmedetomidine demonstrated clinical advantages over midazolam by reducing delirium and ventilation duration but carried a greater risk of bradycardia. Sedative choice should balance efficacy with cardiovascular safety.